1998
DOI: 10.1099/00222615-47-5-441
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to Chlamydia pneumoniae in twins in relation to gender and smoking

Abstract: This study investigated whether gender or smoking has an impact on immune responses to Chlumydiapneumoniue in generally healthy adults. A total of 129 twins (46 twin pairs and 37 single twins) from the Finnish %in Cohort who had previously reported the highest discordance for smoking with their co-twins participated. C. pneumoniue-specific serum IgA and IgG antibody levels were measured by the micro-immunofluorescence test (micro-IF) at admission and 3 months later if the IgA level in the first sample was elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…32,33 In identical twins, C pneumoniae-specific IgA levels were higher, and cell-mediated immunity (measured as a lymphoproliferation response) was lower in the smoking twins than in their nonsmoking cotwins, indicating that chronic C pneumoniae infections in smokers are linked to lowered cell-mediated protective immunity. 34 In our earlier study, 19 smoking significantly increased the risk associated with markers of chronic C pneumoniae infection, and its effect with high levels of CRP was more than multiplicative, showing a high degree of synergy. In the present study, the joint effect of smoking and human Hsp60 IgA antibodies was not negligible, but no synergistic effect was seen.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In identical twins, C pneumoniae-specific IgA levels were higher, and cell-mediated immunity (measured as a lymphoproliferation response) was lower in the smoking twins than in their nonsmoking cotwins, indicating that chronic C pneumoniae infections in smokers are linked to lowered cell-mediated protective immunity. 34 In our earlier study, 19 smoking significantly increased the risk associated with markers of chronic C pneumoniae infection, and its effect with high levels of CRP was more than multiplicative, showing a high degree of synergy. In the present study, the joint effect of smoking and human Hsp60 IgA antibodies was not negligible, but no synergistic effect was seen.…”
Section: Discussionmentioning
confidence: 99%
“…We found that chlamydial antibodies were significantly more common among men and smokers, validating associations noted by others. 23,24 We specifically sought an interaction between C pneumoniae, smoking, and CV events, hypothesizing synergy between smoking and infection. Although the interaction term was statistically significant, the relation between C pneumoniae IgA and CV events persisted only in former smokers or never-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 A plausible explanation is that smoking can compromise lung and bronchial immunity, and thus contributes to the establishment of chronic C. pneumoniae infection. 9,10 Since smoking is a very strong risk factor for lung cancer, any interpretation of the C. pneumoniae-lung cancer relationship in a smoking population should consider the possibility of residual confounding effect even after adjustment using standard statistical techniques. On the other hand, in vitro studies demonstrate that infection with C. pneumoniae readily induces production of reactive oxygen species, TNF-␣, IL-1␤ and IL-8 in alveolar macrophages, 11 thus supporting its potential to act as an inflammatory stimulus and promote lung carcinogenesis.…”
Section: Dear Sirmentioning
confidence: 99%